2017
DOI: 10.1111/jocd.12375
|View full text |Cite
|
Sign up to set email alerts
|

Super pulse CO2 laser therapy for benign eyelid tumors

Abstract: The super pulse CO laser therapy of the benign eyelid tumors provided satisfactory cosmetic results in this study. It is a convenient, cheap, accessible, and well-tolerated alternative to traditional surgery, especially for diffuse tumors, or those positioned close to the lacrimal papillae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Consistent with our previous reports, this study also identified the good clinical response of super pulse CO 2 laser in excision of eyelid benign tumors without any recurrence in the follow-up period [ 1 , 13 ]. Here, the original contribution was to further investigate the potential effects of super pulse CO 2 laser on the meibomian gland.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with our previous reports, this study also identified the good clinical response of super pulse CO 2 laser in excision of eyelid benign tumors without any recurrence in the follow-up period [ 1 , 13 ]. Here, the original contribution was to further investigate the potential effects of super pulse CO 2 laser on the meibomian gland.…”
Section: Discussionsupporting
confidence: 91%
“…Comparing with other laser therapy, super pulse CO 2 lasers enables hemorrhage-free noncontact incisional excision and that producing superior tissue contraction and hemostasis, especially in the deeper lesion removal [ 2 ]. For tumors with special location such as palpebral margins, CO 2 laser surgery keeps the margins in their anatomical position so that entropion or ectropion is not to be reckoned with, showing advantageous in preserving patients' appearance with complete morphology of palpebral margin [ 1 , 5 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Carbon Dioxide pulse laser: Super pulse CO2 laser of 10600 nm wavelength cause tissue photo ablation allowing for simultaneous cutting and hemostasis has become an effective and well tolerated therapeutic method for benign eyelid tumors. 3 In orbital plexiform neurofibromatosis, CO2 laser ablation gives better hemostasis and prevents the loss of natural tissue planes from the tumor's diffuse mode of growth. 4…”
Section: Advances For Benign Tumorsmentioning
confidence: 99%